DETERMINATION OF DISCOUNT RATES IN EVALUATION OF EFFICIENCY OF INVESTMENT PROJECTS IN OIL AND GAS PRODUCTION - Vytvytska, uliana (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article is devoted to the development and substantiation of methodological approaches to determining discount rates in assessing the effectiveness of investment projects in oil and gas production. Since the search, exploration and development of oil and gas fields is a long and capital-intensive process, it is especially important to take into account the time factor, which is carried out by discounting future cash flows (income), using discount rates. Such calculations are especially complicated during financial crises, which have recently increasingly accompanied the development of society. It was found that in the evaluation of investment projects of this type, in order to determine the discount rates, the method of cumulative construction is most widely used. The peculiarities of determining the main components included in the model of cumulative construction in Ukraine have been substantiated - the basic rate of return, which takes into account systematic risks, and the rate of return, which takes into account non-systematic risks inherent a particular oil and gas field. The existing methods of determining non-systematic risks in substantiating discount rates, which are mainly based on the use of expert methods, have been analyzed and the use of correlation-regression analysis have been proposed for this purpose. The most important factors and their weights that form the main risks in the development of oil fields, natural gas and condensate fields and natural gas fields in shale rocks have been identified. For oil fields they are: the depth of productive horizons, the hydraulic conductivity coefficient and water content. For gas and gas condensate fields they are: depth of productive horizons and gas conductivity coefficient. For natural gas fields in shale rocks they are: organic matter content; porosity coefficient; effective power; depth of productive horizons. On this basis, appropriate methods have been developed to assess the magnitude of risks in determining the discount rates and examples of their calculation for oil, gas and gas condensate fields and shale natural gas fields are given.